Fracture and mortality outcomes by osteoporosis treatment route in patients with type 2 diabetes and obesity: a propensity-matched registry study - Rouach, Vanessa; Regev, Ohad; Gortler, Hilary; Greenman, Yona; Chodick, Gabriel; Goldshtein, Inbal (Frontiers in Endocrinology, 2026)
PurposeTo evaluate the real-world effectiveness of antiresorptive osteoporosis pharmacologic treatments on fracture incidence and survival in patients with type 2 diabetes mellitus (T2DM), with subgroup analysis by treatment route.MethodsWe conducted a retrospective cohort study using a national registry of patients with T2DM and osteoporosis. Patients receiving antiresorptive treatments (oral or intravenous/subcutaneous [IV/SC]) were compared to untreated individuals using propensity score matching. The primary outcomes were major osteoporotic fracture (MOF) and all-cause mortality. Cox proportional hazards models were used to assess associations, including subgroup analyses by BMI and HbA1c.ResultsAmong 8,788 matched patients, treatment was associated with significantly lower mortality (adjusted HR 0.86; 95% CI: 0.78–0.94) but not with reduced fracture incidence (HR 1.11; 95% CI: 0.96–1.29). In the treated subgroup (N = 2,960), IV/SC therapy was associated with reduced fracture risk (HR 0.58; 95% CI: 0.35–0.94) but increased mortality (HR 1.63; 95% CI: 1.35–1.96) compared to oral treatment.ConclusionIn this real-world cohort of patients with type 2 diabetes and obesity, osteoporosis treatment was associated with improved survival but not reduced fracture risk. Injectable therapies offered greater fracture protection but were linked to higher mortality, likely due to confounding by indication. Poor adherence may limit the effectiveness of oral treatments in routine care. These findings underscore the need for individualized osteoporosis management strategies in high-risk diabetic populations and raise important considerations regarding the optimal route of administration in real-world settings.